Genetic differentiation in the Mexican endemic Rufous-backed Robin, Turdus rufopalliatus (Passeriformes: Turdidae) - Montaño-Rendón, Mauricio; Sánchez-González, Luis A.; Hernández-Alonso, Germán; Navarro-Sigüenza, Adolfo G. (Zootaxa, 2015)
The Rufous-backed Robin (Turdus rufopalliatus) is endemic to deciduous and semideciduous tropical forests of western Mexico. Of the currently recognized subspecies, T. r. graysoni, from the Tres Marías Islands and nearby coastal Nayarit, has been considered a separate species; however, this treatment has been challenged due to an apparent contact zone on the mainland, although no hybrids have ever been recorded. Here, we use mitochondrial DNA sequences from individuals sampled across the species’ range to assess their phylogeographic relationships. We found reciprocal monophyly between Tres Marías Islands and mainland populations, which share no haplotypes between them. Evolutionary divergence detected within T. rufopalliatus suggests that mainland and island populations have been isolated from each other, and divergence decreases if insular populations are excluded. Demographic parameters suggest that populations are in the process of a rapid expansion from ancestral populations with a lower population size. These results are consistent with morphometric and plumage differences that have been used to recognize the Tres Marías Islands populations from the mainland ones, thus suggesting species status of the island form.